О понятии фонема у О. Э. Мандельштама: Из комментария к статье «О природе слова» [The Notion of Phoneme in Mandel’shtam’s “O prirode slova”] - Larissa Naiditch (Slavica Revalensia)
The article aims to establish the possible source of Osip Mandel’shtam’s understanding of the notion of phoneme as reflected in his article “O prirode slova” (1921—22). Larissa Naiditch suggests that this source should be sought in the lectures by Jan Baudouin de Courtenay, one of the precursors of structuralism. It is known that during his studies at St. Petersburg University, Mandel’shtam attended Baudouin de Courtanay’s classes, thus it is likely that Mandel’shtam could reshape his professor’s ideas.